2021
DOI: 10.30589/pgr.v5i1.348
|View full text |Cite
|
Sign up to set email alerts
|

Users Acceptance of E-Government System in Sintok, Malaysia: Applying the UTAUT Model

Abstract: E-government services have become a vital tool to provide citizens with more accessible, accurate and high-quality services and information. E-government system provides an efficient dissemination of information to people and eases people to communicate directly with government services. The utilization of ICT through e-government enhancing efficiency and effectiveness of service delivery in the public sector. The system is regarded as one of the vital elements to be a developed country. The application of e-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
2
27
0
1
Order By: Relevance
“…Previous studies have found that the higher the public expectation of performance, the greater the motivation to participate in environmental governance. The higher the public EE, the simpler the way to participate in environmental governance E-government platforms [27][28][29]. Therefore, this study proposes the following research hypotheses:…”
Section: Impact Of Public Expectation On E-government Adoption Practicesmentioning
confidence: 99%
“…Previous studies have found that the higher the public expectation of performance, the greater the motivation to participate in environmental governance. The higher the public EE, the simpler the way to participate in environmental governance E-government platforms [27][28][29]. Therefore, this study proposes the following research hypotheses:…”
Section: Impact Of Public Expectation On E-government Adoption Practicesmentioning
confidence: 99%
“…UTAUT theorizes that an individual's behavioural intention to use technology, is influenced by performance expectancy, effort expectancy, social influence, and facilitating conditions (Venkatesh, 2021;Arfi, Nasr, Khvatova & Zaied, 2021). Given its importance in the field of e-government and information system research areas, voluminous researchers have utilized UTAUT in their studies (such as; Venkatesh, 2021;Qaid, Samikoni & Fahmi, 2021;Altalhi, 2021;Maznorbalia & Awalluddin, 2021;Raza et al, 2021;Abbad, 2021;Kagoya & Mbamba, 2020;Almaiah & Nasereddin, 2020;Kagoya & Mkwizu, 2020). For instance, Almaiah and Nasereddin (2020) used UTAUT theory for examining factors affecting e-government services adoption among the citizens of Jordan, while Eapen (2021) used UTAUT theory of adoption for establishing the clinical support systems.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…Additionally, Kurfali et al (2017) used UTAUT in the Turkish study on e-government adoption, while used UTAUT to assess e-government implementation factors in Tanzania and their findings divulged that key attribute from individual users and support from key top managers, were paramount for successful implementation of e-government. Moreover, Maznorbalia and Awalluddin (2021) utilized UTAUT theory in analyzing the acceptance of egovernment system by end-users in Sintok, Malaysia. On the contrary, this study intends to apply UTAUT theory to ascertain the salient determinants of e-government implementation success in Uganda and Tanzania as part of the developing nations on the African continent.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…Selama beberapa tahun terakhir, e-government telah menjadi topik yang menarik perhatian para akademisi dengan munculnya teknologi Web 2.0 (Magro, 2012). Istilah e-government dapat didefinisikan sebagai peningkatan akses dan penyampaian layanan dan informasi pemerintah kepada masyarakat, pelaku bisnis, dan lingkungan pemerintah melalui penggunaan teknologi informasi komunikasi khususnya internet seperti aplikasi berbasis website (Barthwal, 2003;Irawan, 2015;Maznorbalia & Awalludin, 2021) ataupun media sosial (Bonsón et al, 2012;Gao & Lee, 2017). Didorong oleh meningkatnya harapan warga dan kebutuhan inovasi pemerintah, media sosial telah menjadi komponen kunci dari pemerintahan elektronik atau e-government.…”
Section: Pendahuluanunclassified